Locus of control, interest in schooling and self-efficacy as predictors of academic achievement among junior secondary school students in Osun State, Nigeria (2011)
Background: Academic achievement is interestingly an important issue; a fundamental premium upon which all teaching learning activities are measured using some criteria of excellence e.g. good academic performance, poor academic performance and academic failure. Aims: This study examines locus of control, interest in schooling and self-efficacy as predictors of academic achievement of Junior Secondary School Students. Sample: The sample of the study consisted of 500 students comprising 300 boys and 200 girls. These were selected from twenty-five secondary schools through stratified random techniques. The stratification factor used was the class of the students. Method: An ex-post-facto research design is adopted. Three independents variables (Locus of Control, Interest in schooling and self-efficacy) with the dependent variable (academic achievement) are measured with relevant standardized instruments. Two research questions are developed and answered. Results: The results indicate that locus of control, interest in schooling and self efficacy jointly and relatively contribute significantly to the prediction of academic achievement of the Junior Secondary School Students. Conclusion: Based on these findings, the simultaneous need to continuously stimulate the interest of the students and teach them time management, and for teachers to see all the three variables as equally important and to help students improve on them was emphasized.